2019
DOI: 10.1111/apha.13301
|View full text |Cite
|
Sign up to set email alerts
|

O‐GlcNAcylation as a regulator of the functional and structural properties of the sarcomere in skeletal muscle: An update review

Abstract: Although the O-GlcNAcylation process was discovered in 1984, its potential role in the physiology and physiopathology of skeletal muscle only emerged 20 years later. An increasing number of publications strongly support a key role of O-GlcNAcylation in the modulation of important cellular processes which are essential for skeletal muscle functions. Indeed, over a thousand of O-GlcNAcylated proteins have been identified within skeletal muscle since 2004, which belong to various classes of proteins, including sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 116 publications
(180 reference statements)
0
9
0
Order By: Relevance
“…Moreover, O-GlcNAcylation was linked to the modulation of IFs, in particular vimentin 6 and keratin 8/18 filaments 5 , 36 , with a link between O-GlcNAcylation and cell survival in stress condition 34 . In skeletal muscle, O-GlcNAcylation extensively modifies other nucleocytoplasmic and mitochondrial proteins and also myofibrillar proteins 37 . We have previously demonstrated that motor and regulatory proteins are O-GlcNAcylated modulating so the contractile properties of skeletal muscle such as calcium activation parameters 30 , 38 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, O-GlcNAcylation was linked to the modulation of IFs, in particular vimentin 6 and keratin 8/18 filaments 5 , 36 , with a link between O-GlcNAcylation and cell survival in stress condition 34 . In skeletal muscle, O-GlcNAcylation extensively modifies other nucleocytoplasmic and mitochondrial proteins and also myofibrillar proteins 37 . We have previously demonstrated that motor and regulatory proteins are O-GlcNAcylated modulating so the contractile properties of skeletal muscle such as calcium activation parameters 30 , 38 41 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, many O -GlcNAcylated contractile proteins and contractile-related regulatory proteins in sarcomere have been identified [ 67 ]. These key contractile proteins include actin, myosin, MLC and MHC, tropomyosin and troponin, etc.…”
Section: O -Glcnacylation Is An Emerging Mediator Of Contrac...mentioning
confidence: 99%
“…These sites are located in the marginal of the carboxy terminal, which is closely related to the polymerization and the interaction of MHC [ 220 ]. Further evidence is that one of the sites is associated with a hereditary myosin myopathy because its mutation destroys the polymerization of myosin to myomesin, M protein and titin [ 67 ]. Unfortunately, although these specific O -GlcNAcylation changes are associated with calcium sensitivity, they have not been appreciated and studied, and precise O -GlcNAcylated site identification is lacking.…”
Section: O -Glcnacylation Is An Emerging Mediator Of Contrac...mentioning
confidence: 99%
See 2 more Smart Citations